Evaluation and identification of critical success factors in the running of successful food security projects within the Eastern Cape Department of Rural Development and Agrarian Reform, in the Amahlhathi local municipality - Tali, Patrick (Rhodes University, Faculty of Commerce, Investec Business School, 2013)
The challenges of food insecurity and the manner in which it can be addressed is a global concern. Governments throughout the world have strived for means to address global food security either through development of Millennium Development Goals or United Nations protocols. It is a major concern that the South African Government has made it its centre focus to address the challenge of food security. In the Eastern Cape, the Department of Rural Development and Agrarian Reform has embarked on numerous food production programmes in an attempt to address this challenge. It is however noticeable that these attempts somehow did not manage to address their intended purpose. A study of literature with the aim of identifying critical success factors was done. The critical success factors identified and explored were, project management, establishing a clear mission and project objectives, addressing challenges and opportunities of social, environmental and economical sustainability, addressing physiological needs of the beneficiaries, involving the youth and community, role of extension services, training and capacity development, create local partnership and on-going monitoring and evaluation. The factors were then explored through a study of projects from the food production programme in Amahlathi Local Municipality in the Eastern Cape Province. A multiple case study wherein a purposive selection of four food security projects selected from two food security programmes was conducted. A structured questionnaire was used to source the information from all members of the selected projects to evaluate the existence of the critical factors. The main aim was to test whether these factors, if they existed in these projects, contributed to their existence. The findings reveal that none of the identified factors existed in the selected projects and though not proven, the non-existence of these factors has resulted in these projects being in survival mode instead of a sustainable state. A recommendation is made of a further study focusing on a bigger sample wherein these factors could be tested. The study could assist in developing a formal model for the running of these projects successfully.
Keywords: Rural development -- South Africa -- Eastern Cape; Agriculture -- South Africa -- Eastern Cape; Project management -- South Africa -- Stutterheim; Food security -- South Africa -- Stutterheim; Food supply -- South Africa -- Stutterheim